Sitagliptin, An Anti-diabetic Drug, Suppresses Estrogen Deficiency-Induced OsteoporosisIn Vivo and Inhibits RANKL-Induced Osteoclast Formation and Bone Resorption In Vitro - Wang, Chuandong; Xiao, Fei; Qu, Xinhua; Zhai, Zanjing; Hu, Guoli; Chen, Xiaodong; Zhang, Xiaoling (Frontiers in Pharmacology, 2017)
Postmenopausal osteoporosis is a disease characterized by excessive osteoclastic bone resorption. Some anti-diabetic drugs were demonstrated for anti-osteoclastic bone-loss effects. In this study, we tested the skeletal effects of chronic administration of sitagliptin, a dipeptidyl peptidase IV (DPP IV) inhibitor that is increasingly used for type 2 diabetes treatments, in an estrogen deficiency-induced osteoporosis and elucidated the associated mechanisms. We found that sitagliptin effectively prevented ovariectomy-induced bone loss and reduced osteoclast numbers in vivo. We found that sitagliptin suppressed receptor activator of nuclear factor-κB ligand (RANKL)-mediated osteoclast differentiation, bone resorption, and F-actin ring formation in a dose-dependent manner. In addition, sitagliptin significantly reduced the expression of osteoclast-specific markers in mouse bone-marrow-derived macrophages, including calcitonin receptor (Calcr), dendrite cell-specific transmembrane protein (Dc-stamp), c-Fos, and nuclear factor of activated T-cells cytoplasmic 1 (Nfatc1). Further investigation revealed that sitagliptin inhibited osteoclastogenesis by suppressing the AKT and ERK signaling pathways, scavenging ROS activity, and suppressing the Ca2+ oscillation that consequently affects the expression and/or activity of the osteoclast-specific transcription factors, c-Fos and NFATc1. Collectively, these findings suggest that sitagliptin possesses beneficial effects on bone and the suppression of osteoclast number implies that the effect is exerted directly on osteoclastogenesis.